2019
DOI: 10.1177/1460458219833099
|View full text |Cite
|
Sign up to set email alerts
|

Flipped healthcare for better or worse

Abstract: The medical profession is highly specialized, demanding continuous learning, while also undergoing rapid development in the rise of data-driven healthcare. Based on clinical scenarios, this study explores how resident physicians view their roles and practices in relation to informed patients and patient-centric digital technologies. The paper illustrates how the new role of patients alters physicians’ work and use of data to learn and update their professional practice. It suggests new possibilities for develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 42 publications
1
18
0
9
Order By: Relevance
“…As shared decision-making is evolving, it is important to understand what informational support is required in order for the patients to feel sufficiently informed to participate [ 16 ]. Furthermore, prior studies have showed that there is potential, not only for shared decision-making but also for shared learning for the healthcare professionals when parts of the care process are digitalized [ 17 – 19 ]. Blended care may be a possible way forward to achieve this type of support.…”
Section: Discussionmentioning
confidence: 99%
“…As shared decision-making is evolving, it is important to understand what informational support is required in order for the patients to feel sufficiently informed to participate [ 16 ]. Furthermore, prior studies have showed that there is potential, not only for shared decision-making but also for shared learning for the healthcare professionals when parts of the care process are digitalized [ 17 – 19 ]. Blended care may be a possible way forward to achieve this type of support.…”
Section: Discussionmentioning
confidence: 99%
“…The speed of the shift to remote leadership has been accelerated by the global pandemic in 2020. Furthermore, advances in digitalization during the last decade have changed individuals' perceptions and expectations of work, including various novel competences that are associated with a successful remote work environment (Konttila et al, 2019;Vallo Hult et al, 2019).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…9 This shift in healthcare delivery is also consistent with recent moves towards self-management and patient activation within healthcare, whereby accountability for care has changed. [10][11][12] Patients are becoming more involved in self-management, for example, learning how to detect and manage their symptoms, and treatments, and escalation of care associated with their condition, 7,[13][14][15][16][17] and healthcare tasks (e.g., managing medication, organizing care appointments, taking measurements). 18 While some patients may welcome this, 19 there have been concerns that self-management places a burden on patients and families, rather than facilitating shared care.…”
Section: Introductionmentioning
confidence: 99%